2020
DOI: 10.3390/cancers12123651
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MDM2 for Neuroblastoma Therapy: In Vitro and In Vivo Anticancer Activity and Mechanism of Action

Abstract: Background: Neuroblastoma is an aggressive pediatric solid tumor with an overall survival rate of <50% for patients with high-risk disease. The majority (>98%) of pathologically-diagnosed neuroblastomas have wild-type p53 with intact functional activity. However, the mouse double minute 2 (MDM2) homolog, an E3 ubiquitin ligase, is overexpressed in neuroblastoma and leads to inhibition of p53. MDM2 also exerts p53-independent oncogenic functions. Thus, MDM2 seems to be an attractive target for the reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…MDM2, which is located in segment 13–14 of the long arm of chromosome 12, is found in the double minute chromosome of the transformed murine cell line. 31 Accumulating evidence indicates that MDM2 can enhance cellular activity and promote tumor growth, 32 , 33 which could reveal a new therapeutic strategy for EMs. Previous studies indicated that the positivity rate of MDM2 expression in normal endometrium was lower than that in EMs, 34 , 35 which suggests that MDM2 serves as a promoting factor in EMs.…”
Section: Discussionmentioning
confidence: 99%
“…MDM2, which is located in segment 13–14 of the long arm of chromosome 12, is found in the double minute chromosome of the transformed murine cell line. 31 Accumulating evidence indicates that MDM2 can enhance cellular activity and promote tumor growth, 32 , 33 which could reveal a new therapeutic strategy for EMs. Previous studies indicated that the positivity rate of MDM2 expression in normal endometrium was lower than that in EMs, 34 , 35 which suggests that MDM2 serves as a promoting factor in EMs.…”
Section: Discussionmentioning
confidence: 99%
“…However, neuroblastoma seems not to be on that line of response: on the contrary, TP53 mutated alleles seem to increase apoptosis and stop the cell cycle without a prior need for wild-type p53 protein restoration. Not only patients with wild-type TP53 neuroblastoma, but also those with mutant TP53 neuroblastoma might have a good outlook if treated with inhibitors of MDM2 [80,81]. In any case, new strategies are needed to solve this issue, with an open look at the p53/MDM2 interaction, in order to clearly improve the prognosis in neuroblastoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…92 Notably, MDM2 upregulation was observed in various cancers, bringing it a promising target for cancer treatment. 93,94 For instance, inactivating MDM2 suppressed HCC tumor proliferation and invasion and enhanced sensitivity to sorafenib. 95 Further, targeting MDM2-p53 interaction improved adaptive immunity in tumor cells with wild-type p53.…”
Section: Ubiquitin Ligases (E3s)mentioning
confidence: 99%